2022
DOI: 10.1088/1742-6596/2324/1/012007
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress in Intrinsic Self-healing Polyurethane Materials Based on Dynamic Reversible Non-covalent Bonds

Abstract: Polyurethane (PU) is a polymer with great capabilities like high elasticity, low-temperature resistance, wear resistance, and corrosion resistance. However, it will inevitably be damaged in processing or long-term use, which will shorten the service life of the material and increase the potential safety hazards. The widespread use of polyurethanes has given researchers more motivation to make polyurethanes self-healing, thereby eliminating material damage and potential safety hazards to a certain extent. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Up to now, such robust yet healable PUs have been widely synthesized via some distinct strategies, including the incorporation of thermodynamically stable yet kinetically active supramolecular interactions, design of special molecular structures to inhibit crystallization, and regulation of the micro- or nano-structure of the dynamic hard domains. 23 In the following discussion, we will elaborate some advanced strategies related to the design and synthesis of robust yet healable PUs based on different supramolecular interactions.…”
Section: Strategies To Synthesize Healable Polyurethanesmentioning
confidence: 99%
See 1 more Smart Citation
“…Up to now, such robust yet healable PUs have been widely synthesized via some distinct strategies, including the incorporation of thermodynamically stable yet kinetically active supramolecular interactions, design of special molecular structures to inhibit crystallization, and regulation of the micro- or nano-structure of the dynamic hard domains. 23 In the following discussion, we will elaborate some advanced strategies related to the design and synthesis of robust yet healable PUs based on different supramolecular interactions.…”
Section: Strategies To Synthesize Healable Polyurethanesmentioning
confidence: 99%
“…With the development of supramolecular chemistry, researchers have found that supramolecular interactions possess a fantastic dynamic exchange ability attributed to their low bonding energy. 23 Especially, supramolecular interactions are particularly appropriate for healable systems in which no additional stimuli are required. Moreover, they are capable of associating many times under ambient conditions or confined energy input.…”
Section: Physical Healable Pus Based On Supramolecular Chemistrymentioning
confidence: 99%
“…Furthermore, polyurethane with a specific polyphase structure was chosen as the substrate for the polymer electrolyte. Polyurethane, 36,37 known for its exceptional properties such as high elasticity, high‐temperature resistance, corrosion resistance, and ease of processing, has been widely recognized by researchers as a promising material for future polymer electrolytes. The soft chain segment facilitates the conduction of lithium ions, whereas the hard chain segment widens the electrochemical stability window of the electrolyte 38–40 .…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25][26][27] According to the repair type, self-healing materials can be categorized as extrinsic and intrinsic self-healing materials. 28 Extrinsic self-healing generally involves the release of catalysts and monomers stored in capsules or vessels immediately after the material is damaged. 29 After mixing, they begin to polymerize for the purpose of healing the cut.…”
Section: Introductionmentioning
confidence: 99%